Russian Sources on Bosnia and Herzegovina under Austro–Hungarian Rule, 1878–1908: A Short Overview - Pakhomova, Lidia (Historical Studies on Central Europe, 2022)
The article provides a brief overview of Russian historical sources on the history of Bosnia and Herzegovina in the period of the Austro–Hungarian occupation. The body of literature on the subject includes a wealth of work devoted to Austria–Hungary’s modernisation policies in Bosnia and Herzegovina between 1878 and 1914. However, researchers have not yet considered how the Great Powers that made important decisions about the fate of the provinces appraised the governance model of the Austro–Hungarian Empire. Such decisions were made not only on the basis of foreign policy interests and international relations, but also on the basis of observations from the occupied territories. Russian analysts closely explored the development of the provinces in the multi-ethnic Habsburg Monarchy between 1878 and 1908. Russian officials realised that the situation in the multireligious region was very complicated. They analysed both how Austria–Hungary managed this situation as an empire, and their governance model from the point of view of another empire.